2020
DOI: 10.1186/s12884-020-2810-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality, availability and storage conditions of oxytocin and misoprostol in Malawi

Abstract: Background: Postpartum haemorrhage (PPH) is the leading cause of maternal mortality in low-and middle-income countries (LMICs). Oxytocin and misoprostol are used for the prevention and treatment of PPH. However, both medicines are chemically unstable and sensitive to environmental conditions. Previous studies reported a high prevalence of substandard oxytocin and misoprostol preparations in LMICs. Methods: In randomly selected health facilities of four districts of Malawi, the availability of oxytocin and miso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…One brand of misoprostol tablets collected in Rwanda (packaged in double-sided aluminium blisters; manufactured in a country without SRA; not WHO-prequalified) had to be excluded due to extreme deviations from specifications in the assay. Furthermore, Hall [25], Anyakora et al [11] and Hagen et al [12] have reported insufficient misoprostol contents in many misoprostol preparations collected in LMICs. Therefore, quality and/or stability problems are certainly not a rare observation in misoprostol tablets circulating in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One brand of misoprostol tablets collected in Rwanda (packaged in double-sided aluminium blisters; manufactured in a country without SRA; not WHO-prequalified) had to be excluded due to extreme deviations from specifications in the assay. Furthermore, Hall [25], Anyakora et al [11] and Hagen et al [12] have reported insufficient misoprostol contents in many misoprostol preparations collected in LMICs. Therefore, quality and/or stability problems are certainly not a rare observation in misoprostol tablets circulating in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a decrease of the misoprostol content was observed both at 40˚C and 75% RH and at 25˚C and 60% RH (Fig 2). An investigation of the storage conditions of misoprostol tablets in health facilities in Malawi had shown mean kinetic temperatures at the different storage sites ranging from 21.4˚C to 31.0˚C [12]. In view of these observations, a reduction of the stated shelf-life of the originator brand (Table 1) from three to two years may be advisable, especially for those batches which are exported to countries with hot and humid climates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations